2003
DOI: 10.1037/0021-843x.112.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem in schizophrenia: Relationships between self-evaluation, family attitudes, and symptomatology.

Abstract: Participants with schizophrenia (N = 59) were assessed on self-evaluation, symptomatology, and positive and negative affect (expressed emotion) from significant others. An interview-based measure of self-evaluation was used and two independent dimensions of self-esteem were derived: negative and positive evaluation of self. As predicted, negative self-evaluation was strongly associated with positive symptoms, a more critical attitude from family members was associated with greater negative self-evaluation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
177
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 46 publications
17
177
1
6
Order By: Relevance
“…A recent publication highlights the predictive worth of perceived criticism to quality of life and to the patients' conceptions of their illness. 40 Our results are in line with Barrowclough and colleagues, 28 who reported that negative self-concepts mediate the association between family atmosphere and paranoia on a cross-sectional level. Our findings of a vicious cycle presented in figure 1 confirm and extend their findings on a longitudinal level.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A recent publication highlights the predictive worth of perceived criticism to quality of life and to the patients' conceptions of their illness. 40 Our results are in line with Barrowclough and colleagues, 28 who reported that negative self-concepts mediate the association between family atmosphere and paranoia on a cross-sectional level. Our findings of a vicious cycle presented in figure 1 confirm and extend their findings on a longitudinal level.…”
Section: Discussionsupporting
confidence: 82%
“…27 In a crosssectional study, Barrowclough and colleagues 28 found an association between family atmosphere, negative selfevaluation, and positive symptoms. A more critical attitude from family members was associated with a more pronounced negative self-evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Krabbendam et al (2005) found that patients who were hallucinating at baseline were more likely to have psychotic symptoms 3 years later if they also exhibited depressed mood at baseline. Barrowclough et al (2003) found that schizophrenia patients with a negative selfevaluation scored higher on the positive symptoms subscale measuring hallucinations and delusions. Smith et al (2006) examined patients who suffered relapses in psychosis and showed that those with worse depression, self-esteem, and negative beliefs, had persecutory delusions of greater severity.…”
Section: Introductionmentioning
confidence: 93%
“…Each item is scored on a 7-point scale, ranging from 1 (never) to 7 (always). Negative evaluative beliefs about the self have been found to be independently associated with symptoms of psychosis 28,37 ; therefore, we used the negative subscale score as the variable for our analyses.…”
Section: Methodsmentioning
confidence: 99%